The Dark Triad Personality Traits and their Influence on Relationships between Leadership and Employees - Bobrov, Andrei; Motlová, Veronika; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This Bachelor’s Thesis explores how Dark Triad personality traits, narcissism, Machiavellianism, and psychopathy, manifest in leadership and impact employee well-being and workplace relationships. A qualitative approach was adopted, combining an adapted Short Dark Triad questionnaire for participant screening with semi-structured interviews analysed through narrative and thematic methods. The research focused on employees’ lived experiences under toxic leaders across the corporate and hospitality sectors. Findings reveal that Dark Triad leadership consistently erodes psychological safety, trust, and motivation over time. Differences were observed based on which trait dominated leadership behaviour. The study confirms and expands prior theories, highlights practical interventions for organisations, and calls for future research into resilience-building and sector-specific effects.
Vedoucí práce: Veronika Motlová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses